The linking of toxoplasmosis and schizophrenia - Fuller Torrey, Edwin (Folia parasitologica, 2024)
Toxoplasmosis is caused by Toxoplasma gondii (Nicolle et Manceaux, 1908), a coccidian protist (Apicomplexa). It has a strong predilection for infecting the central nervous system. Researchers have therefore investigated its association with several neurological and psychiatric disorders, including Alzheimer's disease, attention-deficit hyperactivity disorder, autism, bipolar disorder, cerebral palsy, depression, Guillain-Barre syndrome, multiple sclerosis, obsessive compulsive disorder, Parkinson's disease, personality disorders, and schizophrenia. Among these disorders the strongest evidence for a role of T. gondii exists for psychosis in general and schizophrenia in particular. This paper reviews the origins of this association, briefly summarises the current evidence in support, and discusses future research strategies.
Keywords: Animals; toxoplazmóza; Cats; epidemiology; lidé; zvířata; brain cysts; Toxoplasmosis; Toxoplasma; Schizophrenia; schizofrenie; Humans